2021
DOI: 10.15218/zjms.2021.012
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and genotyping of Candida albicans involved in vaginal candidiasis among pregnant women in Sulaymaniyah and Erbil cities

Abstract: Background and objective: Vaginal candidiasis is a common infection among pregnant women. The current study aimed to investigate the etiologic species of vaginal candidiasis and the genotypes of C. albicans isolated from vaginal samples among pregnant women in the Kurdistan region of Iraq. Methods: Vaginal swabs were collected from pregnant women admitted to the Maternity hospital in Sulaymaniyah and Erbil cities from March 2016 to December 2018. Candida isolates were identified on CHROMagar medium, then confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Studies have shown that C. albicans is responsible for 80-92% of yeast infections; however, our findings are in contrast to the known prevalence of Candida sp. infection, accounting for around 67.7% and 56.14% prevalence, respectively (Ghajari et al 2018;Shekhany 2021). It was previously believed that Candida only passively aids in developing an opportunistic fungal infection in the presence of an organic weakness or an immunocompromised host.…”
Section: Identification Of Candida Spp Isolatesmentioning
confidence: 99%
“…Studies have shown that C. albicans is responsible for 80-92% of yeast infections; however, our findings are in contrast to the known prevalence of Candida sp. infection, accounting for around 67.7% and 56.14% prevalence, respectively (Ghajari et al 2018;Shekhany 2021). It was previously believed that Candida only passively aids in developing an opportunistic fungal infection in the presence of an organic weakness or an immunocompromised host.…”
Section: Identification Of Candida Spp Isolatesmentioning
confidence: 99%
“…Then place in the thermocycler for 20minute at 95⁰ C, followed by centrifugation for 2 min at 12,000 rpm. The DNAcontaining supernatant was collected and stored at -20 °C for subsequent steps of PCR [21]. The universal primers, forward ITS1-F (5′-TCCGTAGGTGAACCTGCG-3′) and reverse ITS4-R (5′ TCCTCCGCTTATTGATATGC-3′), were utilized to amplify the intergenic spacer regions (ITS) of 5.8 S ribosomal DNA (rDNA) [22].…”
Section: Molecular Identification Of Candida Isolatesmentioning
confidence: 99%
“…For further validation, all the amplicons previously amplified using ITS primers and were 532 bp in size were re-analyzed using a different set of primers CHS1. The chitin synthase gene (CHS1) from C. albicans, 122bp in size, can be amplified by conventional PCR [21]. The colony PCR was carried out with the same procedure previously mentioned using forward CHS1-F (5'-CGCCTCTGATGGTGATGAT-3') and reverse CHS1-R (5'-TCCGGTATCACCTGGCTC-3') primers [23].…”
Section: Confirmation Of the Candida Albicans By Detection Of Chs1 Genementioning
confidence: 99%
“…Another recent study conducted at Maternity Hospital in Erbil City; Iraq found that the prevalence of vulvovaginal candidiasis using culture was 54.66%. The highest number of positive cases 71 (63.4%) was found among the age group of 30 -34 years (Shekhany, 2021) The absolute diagnosis of C. albicans depends on the clinical manifestations is difficult due to mixed with other infections affecting vaginal, including Bacterial vaginosis, Neisseria gonorrhoea and Trichomonas vaginalis. Thus, mycological examinations of vaginal discharges are critical for the initial diagnosis of infection and detection of definitive causative agents (Anderson et al, 2004).…”
Section: Introductionmentioning
confidence: 99%